2021
DOI: 10.3390/su13094815
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Crude Protein with the Supplementation of Amino Acids in the Diet Reduces the Environmental Impact of Growing Pigs Production Evaluated through Life Cycle Assessment

Abstract: Two experiments were performed to determine the digestibility of diets with crude protein (CP) reduction supplemented with amino acids (18.15; 17.15; 16.15 and 15.15%) to growing pigs (30–50 kg), to assess the use of nutrients and account for the manure excretion, and to evaluate the performance, backfat thickness, Longissimus lumborum depth, and plasma urea, aiming to evaluate the environmental impact through life cycle assessment (LCA); for the first time in Brazil interacting experiments were developed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Apart from improvements in growth performance and carcass characteristics, the swine feed industry has been pushed to reduce dietary CP and simultaneously the excretion of nitrogen, which can contribute to greenhouse gas emissions [ 14 , 17 , 18 ]. In this way, it is well established the benefits of reduced CP diets on lowering the environmental impact of pig production [ 14 , 17 , 70 ].…”
Section: Low-cp Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from improvements in growth performance and carcass characteristics, the swine feed industry has been pushed to reduce dietary CP and simultaneously the excretion of nitrogen, which can contribute to greenhouse gas emissions [ 14 , 17 , 18 ]. In this way, it is well established the benefits of reduced CP diets on lowering the environmental impact of pig production [ 14 , 17 , 70 ].…”
Section: Low-cp Formulationsmentioning
confidence: 99%
“…In this way, it is well established the benefits of reduced CP diets on lowering the environmental impact of pig production [ 14 , 17 , 70 ]. However, the relationship between low CP and the environment was not the focus of the present review and may be found elsewhere [ 18 , 77 ]. Meanwhile, new research should continue to focus on strategies utilizing low-CP diets while not compromising growth performance and pig profitability.…”
Section: Low-cp Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber fraction degradation and VFA production is promoted by microbial production for utilization by animals. Protein quality is when all essential amino acids (AAs) are available in correct proportions for a certain individual animal and vice versa [25] and a lack of a certain AA can affect animal productivity through a reduction in feed conversion efficiency due to nutritional deficiency [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of industrial synthetic amino acid technology, supplementary feed grade amino acids have become available for use in livestock diets. A portion of dietary crude protein replacement in poultry and swine diets with grain and synthetic amino acid has been reported to reduce feed cost, and it contributes in the reduction of nitrogen excretion (Chen et al, 2011; Hernandez et al, 2011; He et al, 2016; van Harn et al, 2019; Esteves et al, 2021). However, when pigs are fed low‐protein diets, net energy level of the diet increases as grain and synthetic amino acids replace protein sources in the diet thereby affecting metabolism and feed efficiency leading to increase in fatness (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%